An Experimental Investigation of Slag Foaming of High FexO Slags - Susanna A. C. Stadler; Jacques J. Eksteen; Chris Aldrich (International Mineral Processing Congress, 2003)
"Slag foaming occurs in several pyrometallurgical processes. These processes include steelmaking in basic oxygen steelmaking furnaces and electric arc furnaces as well as various non-ferrous operations like sulphide smelting/converting and base metal slag cleaning. Although slag foaming in steelmaking processes has been extensively researched, little attention has been given to slag foaming in non-ferrous operations. Slag foaming phenomena are complex because often the system consists of three or more phases. With this in mind, factors previously identified as influencing slag foaming were investigated. These include the slag basicity, physical properties of the slag, namely viscosity, surface tension and density, the formation of particles due to undercooling of the slag and the FexO concentration in the slag.Slag foaming was investigated in a vertical tube furnace. The different slags were contained in alumina crucibles and bubbling argon gas through the molten slag induced foaming. The foam height was measured by using stainless steel probes and a voltmeter. The conductivity of the slags made it possible to measure the foam height from the position of the probes when the electrical circuit was completed. Slags were foamed at different temperatures to investigate the effect of solid precipitates.The effect of increasing FexO concentration was found to decrease the foam index due to lower viscosities, but higher surface tension depression appears to have led to increased foam index values at high FexO concentrations."